METHODICAL APPROACHES TO THE ANALYSIS OF THE RESULTS OF RESEARCH ACTIVITIES - S. A. Trushchelev; R. G. Oganov (Рациональная фармакотерапия в кардиологии)
The value of scientific medical information and its impact indicators (researcher’s publishing activity, citation, impact factor, Hirsch index, etc) is considered. Sources of relevant indicators are specified. Data on scientometric indicators of Russian and international scientific cardiology journals are presented.